Penerapan Model CTL (Contextual Teaching And Learning) Melalui Alat Peraga Torso dalam Peningkatan Hasil Belajar Pada Mata Pelajaran IPA Kelas V di SDN Muara Bumban 1 Kabupaten Murung Raya - Erisma Nurhaliza (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2019)
So that the formulation of this problem is 1) How is the application of the CTL (Contextual Teaching and Learning) model through the Torso Props Class V at SDN Muara Bumban 1, Murung District, Murung Raya District. 2) Is there an increase in student learning outcomes after the application of the fifth grade CTL (Contextual Teaching and Learning) model at SDN Muara Bumban 1, Murung District, Murung Raya Regency. This study aims to determine: 1) The application is carried out using the CTL (contextual taching and learning) learning model using torso props in the fifth grade natural science subjects at SDN Muara Bumban 1, Murung District, Murung Raya District. 2) To find out the increase in student learning outcomes after using the CTL (Contextual Teaching and Learning) model class V at SDN Muara Bumban 1, Murung District, Murung Raya Regency. This study uses a mixed methodology (mixed methodology). The population and sample data in this study were 15 students. Data collection techniques used in this study were observation, objective tests (pre-test and post-test) and documentation. The results of this study indicate that: 1) The application is carried out using the CTL (contextual taching and learning) learning model using torso teaching aids that students tend to be active during learning and listening to what is explained and conveyed by the teacher. 2) There is an increase after is 43,733 receiving treatment (treatment) with an average post-test value that is equal to 87.2 and N-gain value of 0.767 with moderate criteria.